(untitled) (Global Journal of Medical Research, 2024)
Editorial The name bipolar disorder says it all it is uncontrollable swich between good and bad moods It is considered mental disease but there is nothing wrong with the mental abilities of these people Since emotions are involved it should be called psychic disease ln the past the bipolar people were called possessed by Evil Spirit because the ancients were considering the good mood as dominating good Spirit and the bad mood as dominating bad Evil Spirit After the First World War they were called schizophrenics and their disease called schizophrenia Now the same people are called individuals with bipolar disorder